Young carers in England: Findings from the 2018 BBC survey on the prevalence and nature of caring among young people. (24th May 2019) - Joseph, Stephen; Kendall, Claire; Toher, Deirdre; Sempik, Joe; Holland, Jennifer; Becker, Saul
Abstract: Background: Many young people are involved in caring for parents, siblings, or other relatives who have an illness or disability. The aim of this study was to estimate the prevalence of caring by young people in England. Method: A national survey of 925 English young people was conducted using the 18‐item survey version of the Multidimensional Assessment of Caring Activities Checklist for Young Carers. Results: Around 7% of young people were identified as doing at least a high amount of caring activity and 3% a very high amount. Most frequently, caring by a young person is for a mother or a sibling, with a physical disability. Caring activity consisted mostly of domestic activities, household management, and emotional care. Conclusion: This study provides the most up to date and methodologically sophisticated survey data on the prevalence of young caring in England, with implications for policy and practice.